Results of pasture monitoring research - D, Bolormaa; D, Lkhagvasuren; J, Gantuya; L, Gankhuyag; R, Altanzul (Mongolian Journal of Agricultural Sciences, 2018)
Rangeland deterioration and restoration management has been one of the prominent issues. The present study focuses on the composition, cover, and yields accumulation of rangeland plant species from different ecological zones and subzones. Pasture yield in Mongolia varies in ecological zones and subzones (p≥0.001), so 39 sheep, during the summer, comfortably graze in one-hectare area in high mountain zone, - 72 in forest steppe, 21 in steppe and 13 in arid steppe area respectively. Whereas types and cover of plant species in high mountain rangelands are more than other areas, yield accumulation is most in forest steppe. The impact of climate change has dramatically increased recent years, considerably affecting on pasture plant cover and yield. During a dry season or period of drought, amount of yield reduces 40% in high mountain zone; 49% in forest steppe, 52% in semi-arid steppe and 55% in arid steppe. Since rangeland productivity varies due to the nature and climate in the ecological zones and subzones, pasture shall be utilized under appropriate policy that regulates this depending on its capacity, resource and natural and climate feature of area.